Internalisasi Nilai-Nilai Humanistik dalam Kurikulum Merdeka di Sekolah Dasar Negeri Sebatik - Aliya Ramdani; Nana Syafika; Nur Wahyunisa; Riska Murni Saputri; Susiana (Syamil: Jurnal Pendidikan dan Pemikiran Islam, 2024)
Education at the Elementary School (SD) level has a strategic role in shaping students' character and personality. This study aims to explore the application of humanistic values ​​in education at SDN Sebatik and its impact on students' character development. The research method used is a qualitative approach with a case study, involving interviews, observations, and document analysis to understand the implementation of humanistic values ​​in the curriculum and social interactions in schools. The results of the study show that SDN Sebatik integrates humanistic values, such as empathy, tolerance, honesty, and togetherness, in the Merdeka Curriculum through experiential learning, group activities, and multicultural education. Teachers act as role models in instilling these values, while schools implement policies that support inclusive education and student character development. The success of the implementation of humanistic values ​​is reflected in the increase in student engagement in learning, their social skills, and their positive attitudes towards others. The implications of this study indicate that humanistic-based education can create a harmonious learning environment and support student development holistically. Recommendations include strengthening school policies in supporting humanistic values ​​as well as training for teachers to implement this approach more effectively.